Dramaturgi koruptor: Analisis framing pada pemberitaan Lukas Enembe di media detik.com - Khuzaimah, Khuzaimah; Ciddan, Harrel; Sadewo, Fransiscus Xaverius Sri (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2023)
Indonesia occupies the fifth position of the most corrupt country in Southeast Asia. Various reports of corruption are widely circulated in the media. Corruption suspects sometimes display conditions that differ from what they should be. As was done by Lukas Enembe, who failed to summon the KPK several times because of his health condition. However, many media reports that Lukas is in good health and can even travel abroad. This makes researchers interested in knowing the media framing of corruptors. This study aims to determine the dramaturgy of corruptors and news framing on detik.com media. The method used is framing analysis from Robert M. Entman, with a qualitative approach model. The research data was obtained from the results of news analysis on media detik.com. Researchers also use secondary data as journal articles, books, and other literature on the internet. Data were analyzed using Robert M Entman’s framing analysis model. The results of the study show that media detik.com frames the news on corruption by Lukas Enembe by providing space for the KPK to refute the allegations made by the suspect’s family. There is dramaturgy performed by Lukas, as well as the front stage, which states that he is sick but behind that he can move around healthily in detention. This research has a function of providing information to the public about media neutrality in presenting news, including corruption news. In addition, this research can be used as consideration and knowledge for the KPK in performing investigations that corruptors can perform dramaturgy in the investigation process.